Approaches for Excision of Intramasseteric Nodules. Issue 1 (January 2019) - Aizawa, Tetsushi; Kubo, Satoshi; Azuma, Ryuichi; Kiyosawa, Tomoharu
Abstract : Abstract: Developmental lesions, including benign or malignant tumors, rarely arise in the masseteric region. This retrospective study was performed to evaluate the adequacy of different surgical approaches in a series of patients with lesions in the masseteric region. The surgical methods, postoperative complications, pathological diagnosis, and aesthetic outcome were compared in 4 patients who underwent excision of intramasseteric mass lesions. A flap was elevated in 3 patients and direct incisional resection was performed in 1 patient. Two patients underwent incisional biopsy to exclude malignancy before the total excision was performed. The final diagnosis was hemangioma in 3 patients and schwannoma in 1 patient. All patients were satisfied with the aesthetic results and there were no major complications. In conclusion, surgery with skin flap elevation was concluded to be the best approach based on overall assessment of technical considerations, complications, and the cosmetic outcome. However, the surgeon should not hesitate to perform direct incisional biopsy when malignancy needs to be excluded.